Analysis of Determination Transit Oriented Development Areas (TOD) at Light Rail Transit (LRT) Stations in Palembang City Review on Environmental Aspects - Ramanda Muhammad, Ifan; Widyaningsih, Nunung (ASTONJADRO, 2023)
The concept of Transit Oriented Development (TOD) at the Light Rail Transit (LRT) station in Palembang City in terms of Environmental Aspects. This study discussed the city of Palembang which already has several transit-based transportation such as Bus Rapid Transit (BRT) and Light Rail Transit (LRT) as a solution to overcome existing congestion. The several areas that still have congestion points and have not been able to be minimized, namely; (1) Bumi Sriwijaya, (2) Cinde Market, (3) 16 Ilir Market, and (4) Jakabaring. At this location, there were several problem phenomena that are still faced in the implementation of the existing TOD where the community does not use an integrated transportation system, This research used Process Hierarchy Analysis (AHP) method. This research was the preparation of evaluation and analysis of the determination of the Transit Oriented Development (TOD) area in the city of Palembang in terms of environmental aspects based on the AHP decision-making method. The research locations reviewed in this study are densely populated areas. In this study using a quantitative research approach. A quantitative approach used to analyze the determination of the Transit Oriented Development (TOD) area in Palembang City in terms of environmental aspects using AHP decision-making analysis techniques in compiling research discussions. The potential as location of the Transit Oriented Development (TOD) area in Palembang City was the Pasar 16 Ilir area (location 3). This area had the highest potential from other areas after the AHP data processing was carried out against the three main criteria for determining the TOD area.